Do managers capture the value they create? Drivers of managers' value capture in a large retail chain. (1st April 2022) - De Stefano, Federica; Bidwell, Matthew; Camuffo, Arnaldo
Abstract: Research Summary: We investigate the relationship between value creation and value capture among frontline managers. Using longitudinal data from a restaurant chain, we find that those managers who persistently create more value for the firm capture just 0.5% of that extra value through their pay. We explore the reasons for this limited managerial value capture using an abductive approach. We find some evidence that value capture may be limited by lack of alternative employment opportunities. More extensive evidence suggests that the employer often struggled to identify individual contributions to value creation, limiting managerial rewards. We discuss the theoretical implications of such limited managerial value capture for the strategic human capital literature. Managerial Summary: Frontline managers can differ in how much they contribute to firm profitability. Do those managers who contribute the most to firm performance also capture those benefits back through higher pay? In a study of restaurant managers, we find that managers differ substantially in the profits that they create, but that the most profitable managers only capture 0.5% of the extra profits they create. We also find evidence that the firm often fails to identify which managers are the most persistently profitable, potentially reducing the rewards paid to those managers. By demonstrating that differences in performance are not balanced by differences in pay, we show how high‐performing managers can be an important strategic resource for organizations.